Implementasi Pendekatan Transdisipliner Dalam Pembelajaran Wahdatul Ulum di UIN Sumatera Utara Medan (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2026)
This research is motivated by the limited studies on the transdisciplinary approach in teaching Wahdatul Ulum at UIN Sumatera Utara Medan, even though it has a significant impact on UIN Sumatera Utara as a state Islamic university (PTKIN) with strategic potential to implement this approach. However, limitations are still found in its implementation. This study aims to examine the practice of implementing the transdisciplinary approach in teaching the Wahdatul Ulum course, especially in the Islamic religious education (PAI) study program at UIN North Sumatra. This study used a phenomenological qualitative design to understand students' experiences regarding the implementation of a transdisciplinary approach in the Wahdatul Ulum course at UIN North Sumatra. Data were collected through semi-structured interviews and documentation. Analysis was conducted through data reduction, data presentation, and drawing conclusions within the framework of phenomenological analysis. Data validity was strengthened through source triangulation and member checking. All procedures adhered to research ethics, including participation consent and identity confidentiality. The findings imply that lecturers need to enhance their role as facilitators capable of managing cross-disciplinary learning and providing examples of real knowledge integration. At the PAI study program curriculum level, it is necessary to strengthen designs based on learning outcomes that support scientific synthesis, including the provision of modules and collaborative learning scheme.